Lean and productivity in the financing of health services - Kılıçarslan, Menekşe; Özyurt Kaptanoğlu, Rana (My University, 2019)
Financing health services plays an important role in ensuring control and the utilization of expenditures. Because of this, the appropriate selection of the financing should be done with utmost care. Hospitals debts have doubled in the last four years. The most important reason of this is that patients can easily reach all of the hospitals, necessary tests and surgeries that the performance system has brought. When the problems of hospitals are analysed from a general perspective, because of the SSI and performance system, institutions have entered in a severe bottleneck and have been severely restricted (Erkol and Ağırbaş, 2011: 88). The same process continues in the official institutions. In the private institutions, the situation has started to be somewhat different, and the differences arising from case-by-case payments have begun to be received from the patient underhandedly.

Sağlık hizmetlerinin finanse edilmesi, kontrolün sağlanmasında ve harcamaların kullanılmasında önemli bir rol oynamaktadır. Bu nedenle uygun finansman seçimi özenle yapılmalıdır. Son dört yılda hastaneler borçları iki katına çıkarmıştır. Bunun en önemli nedeni, hastaların performans sisteminin getirdiği tüm hastanelere, gerekli testlere ve ameliyatlara kolayca ulaşabilmeleridir. Hastanelerin sorunları genel bir bakış açısıyla analiz edildiğinde, SGK ve performans sistemi nedeniyle kurumlar ciddi bir darboğaza girmiş ve ciddi şekilde kısıtlanmıştır (Erkol ve Ağırbaş, 2011: 88). Resmi kurumlarda da aynı süreç devam etmektedir. Özel kurumlarda durum biraz farklılaşmaya başlamış ve duruma göre ödemelerden kaynaklanan farklılıklar hastadan alınmaya başlanmuştır.
Sağlık hizmetlerinin finansmanında yalın ve verimlilik
Keywords: Budget; SSI (Social Security Institution); Health; Finance; Bütçe; SGK (Sosyal Güvenlik Kurumu); Sağlık; Finans